Arctic National Wildlife Refuge (ANWR): Legislative Actions in the 110th Congress - Corn, M. Lynne; Roberts, Elizabeth A. (Library of Congress. Congressional Research Service., 2008)
This report provides information on Arctic National Wildlife Refuge (ANWR) and its Controversies for the 110th Congress.